Indonesia’s Cultural Diplomacy in Introducing Subak and Spice Routes at World Water Forum 2024 - Puspitasari, Ayu; Rangga, Muhammad; Wicaksono , Tito Prasetio; Luerdi, Luerdi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2025)
Culture has been an important element in nations' relations, so it is often exploited as a tool of diplomacy. Cultural assets have now been introduced in many international forums or events. This study aims to describe cultural diplomacy by Indonesia through an exhibition of Subak and spice routes at the event of the 10th World Water Forum hosted by the nation. This research applied the qualitative method and the concept of cultural diplomacy. The findings suggest that Balinese values and cultural norms turned to soft power that Indonesia’s administration used as cultural diplomacy to gain recognition of the culture. In addition, the study suggests that participating in and hosting the event demonstrates Indonesia’s commitment and role in the global water crisis. Indonesia showcased the best practice of water mangement integrated local wisdom and proposed inititives embolding global collective actions.